A New Fragment of Diocletian's Currency Regulation from Aphrodisias*. (November 2015) - Chaniotis, Angelos; Fujii, Takashi
Abstract: An inscription found in Aphrodisias in 2014 is recognized as a fragment of a dossier concerning Diocletian's currency regulation. This dossier, probably consisting of two edicts and a letter, was inscribed on two blocks of the civic basilica wall. The new fragment belongs to the letter that accompanied the edicts. The reference to the diocese suggests that the letter was addressed to the rationalis of the diocese of Asia. The new fragment belongs to the bottom right corner of the upper block. Thus, it provides new possibilities for the reconstruction of the fragments of the upper block.